IMPLIKASI ARTIFICIAL INTELLIGENCE TERHADAP NILAI DAN ETIKA PEMBELAJARAN PAI PADA MAHASISWA GENERASI Z - Muksalmina; Salami; Nurbayani (Fakultas Tarbiyah IAI Almuslim Aceh, 2025)
This study aims to identify the patterns of AI usage in Islamic Religious Education (PAI) learning among Generation Z students, analyze its implications for their understanding of Islamic values, and evaluate the ethical challenges that arise in AI-based PAI learning. A descriptive qualitative method was employed, with data collected through in-depth interviews and focus group discussions. The findings reveal that although AI improves accessibility and learning efficiency, it also poses significant risks to students’ independent critical thinking, contextual comprehension of Islamic teachings, and academic integrity. This study provides recommendations for developing an ethical framework for AI utilization in PAI learning that integrates Islamic values and transformative pedagogy.